Pulsating hydromagnetic flow of Au-blood micropolar nanofluid in a channel with Ohmic heating, thermal radiation and heat source/sink - Rajkumar, Devendiran; Subramanyam Reddy, Anala (Nonlinear Analysis: Modelling and Control, 2022)
The current work deals with the pulsating flow of Au-blood micropolar nanofluid with the existence of thermal radiation and Joule heating. Micropolar fluid is addressed as blood (base fluid) and Au (gold) as a nanoparticle. The flow has been mathematically modeled, resulting in a delicate system of partial differential equations (PDEs). A perturbation technique is used to convert the PDE system into ordinary differential equations (ODEs), which are subsequently solved by using the shooting method with the Runge–Kutta fourth-order scheme. The effects of various parameters on the velocity, microrotation, temperature, and heat transfer rate of Au-blood nanofluid are graphically depicted and explored successively. The obtained findings bring out that the velocity of nanofluid decreases over a rise in the coupling parameter, magnetic field, and nanoparticle volume fractions. The temperature is reducing with an increment of radiation parameter, frequency parameter, coupling parameter, magnetic field, and volume fraction of nanoparticles. Further, the results show that the Nusselt number against frequency distribution increasing with the rising values of the Eckert number.